2021
DOI: 10.3390/rs13163267
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Dynamics and Climatological Drivers in Ethiopia at the Turn of the Century

Abstract: Global change, particularly climate change, poses a risk of altering vegetation composition and health. The consequences manifest throughout Earth’s system as a change in ecosystem services and socioecological stability. It is therefore critical that vegetation dynamics are monitored to establish baseline conditions and detect shifts. Africa is at high risk of environmental change, yet evaluation of the link between climate and vegetation is still needed for some regions. This work expands on more frequent loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 70 publications
2
7
0
Order By: Relevance
“…For instance, panel multi‐variate regression models use multi‐date observations of the same locations or spatial units to help understand which candidate predictors are most likely responsible for explaining ‘change’ while controlling for time‐invariant factors (e.g. Gaughan et al, 2013; Muir et al, 2021). Among other methods, structural equation models (SEMs) developed from earlier applications of path analysis (Fan et al, 2016; Wright, 1921) have been increasingly used to test hypotheses about direct and indirect relationships among ecological variables.…”
Section: Improving Mechanistic Understanding Of Phenology Across Scalesmentioning
confidence: 99%
“…For instance, panel multi‐variate regression models use multi‐date observations of the same locations or spatial units to help understand which candidate predictors are most likely responsible for explaining ‘change’ while controlling for time‐invariant factors (e.g. Gaughan et al, 2013; Muir et al, 2021). Among other methods, structural equation models (SEMs) developed from earlier applications of path analysis (Fan et al, 2016; Wright, 1921) have been increasingly used to test hypotheses about direct and indirect relationships among ecological variables.…”
Section: Improving Mechanistic Understanding Of Phenology Across Scalesmentioning
confidence: 99%
“…Furthermore, Muir et al (2021) investigated vegetation change using MODIS satellite data over the entire country of Ethiopia, observing declines in the NDVI, with the greatest change during the dry season and concentrated in the northern semi-arid regions of the country. Similarly, Measho et al (2019) noted a decreasing NDVI at 57.15% and 58.74% of all the pixels, respectively, for the annual main growing seasons in the semi-arid region of Eritrea.…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia many studies have highlighted differences in NDVI changes and their response to climatic factors (Kourouma et al 2021;Muir et al 2021;Liou and Mulualem 2019). Therefore, those studies suggested that rainfall is the most crucial elements so as to characterize impact of drought on environment in east Africa, particularly semi-arid region of Ethiopia.…”
Section: Introductionmentioning
confidence: 99%